The cooked and the raw: A taphonomic study of cooked and burned fish. (August 2016) - Zohar, Irit; Ovadia, Ahiad; Goren-Inbar, Naama
Abstract: This article presents an experimental approach to examining the effects of different heating temperatures (300–900 °C) on the survivorship of cranial skeletal elements and pharyngeal teeth in modern black carp. In addition to the traditional visual inspection of the taphonomy of skeletal remains, we examined the potential use of SEM and powder X-ray diffraction (XRD) as an accurate method for assessing the thermal alteration of teeth following heating. Our findings reveal that differential preservation of thermally-heated fish can be identified from remains disposed of in an open fire. We found a relationship between the anatomical location of bones and their probability of surviving the heat. Overall, pharyngeal teeth exhibited the best survival rate, up to 900 °C. The findings from this experiment and the regression equation obtained from the XRD can be applied in future research for identifying cooking and waste disposal practices for carp remains found in archaeological contexts. Graphical abstract: Highlights: We demonstrate the effects of heating temperature (300–900 °C) on the survivorship of carp bones and teeth. We used SEM and powder X-ray diffraction (XRD) to identify thermally altered teeth. We identified a relationship between the anatomical location of bones and their probability of surviving the heat. Pharyngeal teeth exhibited the best survival rate, up to 900 °C.